(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
A photo-catalytic composite material incorporating rice husk ash (RHA) and TiO2 (RHA:TiO2 = 75:25 and 50:50) has been developed and used to investigate the photodegradation of the well-known dye pollutant, methylene blue (MB). Photodegradation was monitored in the dark and under illumination using a halogen lamp as well as sun light to facilitate photodegradation. Both the dark reaction and photo- mineralization processes were evaluated in terms of kinetic study which revealed the validation of first-order kinetics. A parallel measurement of chemical oxygen demand (COD) was also performed for a better understanding of the degradation process. The higher degradation rate in the sun light offers an easy-to-use and environment friendly approach for the treatment of dye stuffs. However, the overall phototdegradation mechanism involved the participation of both the anodic (h+ consumption) and cathodic (e- consumption) processes which were responsible for the degradation of MB and consumption of dissolved oxygen respectively. Key words: Photo-degradation; Composite plate; Rice husk ash, Methylene blue; Adsorption. DOI: http://dx.doi.org/10.3329/bjsir.v46i1.8100 Bangladesh J. Sci. Ind. Res. 46(1), 17-26, 2011